PENINGKATAN KOMPETENSI TAKHRIJ HADIS MAHASISWA ILMU HADIS UINSA SURABAYA MELALUI PELATIHAN OPTIMALISASI MAKTABAH SYAMILAH - Ferdy Pratama; Fahrur Razi; Erfan Fausi; Mochammad Rafi’i Akbar; Alvin Afifah; Edoardo Arta Diansyah; Sahal Aqil Abrori (Jurnal Abdimas Bina Bangsa, 2024)
The development of technology and information has influenced various aspects, including the scientific learning aspect of hadith. The use of this technology can go hand in hand with how students of the hadith science study program at UIN Sunan Ampel Surabaya carry out an efficient and effective process of takhrij hadith by using the Maktabah Syamilah application. Using the Maktabah Syamilah application in the hadith takhrij process can be quite helpful with the various features contained in the Maktabah Syamilah application. This training activity has three stages, namely preparation, implementation and evaluation. The methods used in this training are participation, discussion and direct practice with assistance to provide solutions to existing problems. As a result of this service, the use of technology based on the Maktabah Syamilah application provides new knowledge and skills and the process of takhrij hadith is carried out more optimally. The importance of training that supports the learning process of students in the Hadith science study program should be carried out in stages because it requires quite a lot to directly apply the various features in the Maktabah Syamilah application